Tau phosphorylation in human brain: relationship to behavioral disturbance in dementia. - Guadagna, S; Esiri, M; Williams, R; Francis, P (2012)
Agitation and aggressive behavior are common symptoms of Alzheimer's disease (AD), and tangle density in frontal cortex is a possible regional substrate of these behaviors. To investigate this further, 16 AD patients, 8 patients with non-AD dementia, and 13 age-matched control subjects for frontal cortex and, respectively, 21, 7, and 6 patients for parietal cortex were analyzed for tau and phospho-tau by enzyme-linked immunosorbent assay (ELISA). Agitation/aggression was determined by the Present Behavioural Examination. In a subset of cases, glycogen synthase kinase-3β (GSK-3β) phosphorylation and protein phosphatase 2A (PP2A) expression were measured. Phospho-tau and the phospho-tau/total tau ratio were elevated in AD in both cortical regions. In keeping with our hypothesis, the phospho-tau/total tau ratio was elevated in the frontal cortex of those patients with agitation/aggression during life, and there was a significant correlation (p = 0.024) between these behaviors and the phospho-tau/total tau ratio in the cortex. PP2A expression was lower (p < 0.01) in the frontal cortex of patients with high tau phosphorylation. This study confirms a link between tau phosphorylation and agitation/aggression and suggests that reducing tau phosphorylation may provide symptomatic relief.